Pengaruh Air Rebusan Daun Salam Terhadap Pasien Penderita Hipertensi - Yusipa, Rica; Yustiani, Revita; Hartono, Rudi; Siti Risma, N; Fauziah, Sifa (Lentera : Jurnal Ilmiah Kesehatan dan Keperawatan, 2022)
Hypertension is an increase in systolic blood pressure of more than 140 mmHg and 90mmHg diastolic. Hypertension is often referred to as the "silent killer" because it rarely shows signs and if it is suffered for a long time, it can cause various complications. Hypertension requires appropriate treatment, both from a pharmacological and non-pharmacological. The literature search used a strategy with keywords the effect of bay leaf boiled water on patients with hypertension. From 10 articles it is described that there is a relationship between the effect of bay leaf boiled water on patients with hypertension by drinking it every day. Based on the results of the study that the use of non-pharmacological therapy by giving bay leaf boiled water to hypertensive patients is considered effective for lowering blood pressure. Bay leaves are proven to have various pharmacological activities as antifungal, antibacterial, anti-inflammatory, antioxidant, anti cholesterol, antidiabetic, antimalarial, anti-hyperuricemia antidiarrheal.